The End of Textiles Quotas : A Case Study of the Impacton Bangladesh - Mlachila, Montfort; Yang, Yongzheng (Washington, D.C. : International Monetary Fund, 2004)
This paper evaluates the effects on the Bangladeshi economy of phasing out textile and clothing (T and C) quotas currently maintained by industrial countries. The planned abolition of the quotas under the Agreement on Textiles and Clothing in 2005 will alter the competitiveness of various exporting countries. Bangladesh relies heavily on textile and clothing exports and is potentially very vulnerable to this change in competitiveness. Based on assessments of quota restrictiveness and export similarity, and an analysis of its supply constraints, the paper concludes that Bangladesh could face significant pressure on its balance of payments, output, and employment when the quotas are eliminated.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet